PENERAPAN METODE PBL (PROJECT BASED LEARNING) DALAM PENDIDIKAN JASMANI - Muhammad Akbar Syafruddin (STKIP Melawi, 2024)
Abstract: This research is a qualitative descriptive study which aims to find out the benefits of applying the Project Based Learning (PBL) method in Physical Education learning. The method used in this research is a literature review or library study which utilizes various media such as researchgate, elsevier, and Google Scholar to search for information related to the theme raised. The search for articles that were sources of information in this research used the keywords Project Based Learning (PBL) and Physical Education. A total of 16 articles were used in this research to answer questions according to the themes raised. Based on the literature study, it can be concluded that the application of the Project Based Learning (PBL) method in Physical Education learning can increase learning motivation, self-confidence, creativity, collaboration ability, self-regulation, innovation ability, independent thinking, and student learning outcomes. So it can be stated that the Project Based Learning (PBL) method is very appropriate to use in the Physical Education learning process.Keywords: Learning Methods, Project Based Learning (PBL), Physical Education.Â Abstrak: Penelitian ini adalah penelitian deskriptif kualitatif yang bertujuan untuk mengetahui bagaimana manfaat penerapan metode Project Based Learning (PBL) dalam pembelajaran Pendidikan Jasmani. Metode yang digunakan dalam penelitian ini adalah literature review atau studi pustaka yang memanfaatkan berbagai media seperti researchgate, elsevier, dan google scholar dalam mencari informasi yang berkaitan dengan tema yang diangkat. Pencarian artikel yang menjadi sumber informasi dalam penelitian ini menggunakan kata kunci Project Based Learning (PBL) dan Pendidikan Jasmani. Sebanyak 16 artikel digunakan dalam penelitian ini untuk menjawab persoalan sesuai dengan tema yang diangkat. Berdasarkan studi pustaka dapat disimpulkan bahwa penerapan metode Project Based Learning (PBL) dalam pembelajaran Pendidikan Jasmani dapat meningkatkan motivasi belajar, kepercayaan diri, keratifitas, kemampuan kolaborasi, self-regulated, kemampuan berinovasi, berpikir mandiri, dan hasil belajar peserta didik. Sehingga dapat dinyatakan bahwa metode Project Based Learning (PBL) sangat tepat digunakan dalam proses pembelajaran Pendidikan Jasmani.Kata Kunci: Metode Pembelajaran, Project Based Learning (PBL), Pendidikan Jasmani.